Profitable Growth Release Internal Growth Brakes and Bring Your Company to the Next Level - Quelle, Guido; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Almost every company wants to grow - at least officially. Shareholders are demanding further growth and no management team would deny that the growth of their company is one of the top issues they are working on every single day. However, there are barriers to growth, and these are not only external barriers. Most often it is not the economy, not the market and not the customer who just "hasn't got it." The main barriers can be discovered inside every company, because growth always comes from within. If the organization is not ready to grow, initiatives to increase market share, to enter new markets, and/or to increase profitability are destined to fail. This book systematically addresses the main internal barriers to growth and provides practical guidance not only for discovering these barriers, but to systematically overcoming them.
How Long Do you Want to Tolerate the Fact That Your Organization Is Hindering Growth? -- Is Your Organization Ready for Growth? -- Take a Good Look at Your Marketing Department - Do You See Creative Geniuses or Conceptional Pros? -- Is Your Sales Organization a Dark Silo or a Real Growth Driver? -- Is Your R&D Department Focused on Growth, or just Its Own Ego -- Is Your Purchasing Department Rewarded for Being Bean Counters - or for Delivering Quality? -- For Support Departments, Changes Are a Nightmire -- A Good Product Isn't Enough - You Need a Growth Process -- Non-Profit Organizations - "No Profits" Is No Excuse -- The Most Effective Strategies for Blocking Growth -- Still Searching for a Growth Motor? - Try Looking in the Mirror!.
Keywords: Economics; Industrial management; Economics/Management Science; Business Strategy/Leadership.; Management/Business for Professionals